A New Pseudoguaiane-type Sesquiterpene and Potential Genotoxicity and Antigenotoxicity Effect of the Soft Coral Litophyton arboreum Extract - Hawas, Usama W.; Abou El-Kassem, Lamia T.; Fahmy, Maha A.; Farghaly, Ayman A.; Hassan, Zeinab M. (Letters in Organic Chemistry, 2018)
A new sesquiterpene, litopharbdiol along with five known metabolites of terpenes and sterols were isolated and identified from the methanolic extract of the Red Sea soft coral Litophyton arboreum. The structures of the isolated compounds were elucidated on the basis of their 1D- and 2DNMR and MS spectral data. In parallel, the total extract was evaluated for its in vivo genotoxicity and antigenotoxicity against the mutagenicity induced by the anticancer drug cyclophosphamide (CP). The extract was found to be safe and nongenotoxic at 100 mg/kg b.wt. Moreover, the mice group of CP pretreated with the extract (100 mg/kg b.wt) showed significant reduction in the percentage of chromosomal aberrations induced in bone marrow and mouse spermatocytes.
Keywords: antigenotoxicity